NASA’s Earth Observing Data and Information System – Near-Term Challenges - Jeanne Behnke; Andrew Mitchell; Hampapuram Ramapriyan (Data Science Journal, 2019)
NASA’s Earth Observing System Data and Information System (EOSDIS) has been a central component of the NASA Earth observation program since the 1990’s. EOSDIS manages data covering a wide range of Earth science disciplines including cryosphere, land cover change, polar processes, field campaigns, ocean surface, digital elevation, atmospheric dynamics and composition, and inter-disciplinary research, and many others. One of the key components of EOSDIS is a set of twelve discipline-based Distributed Active Archive Centers (DAACs) distributed across the United States. Managed by NASA’s Earth Science Data and Information System (ESDIS) Project at the Goddard Space Flight Center, these DAACs serve over 4 million users globally. The ESDIS Project provides the infrastructure support for EOSDIS, which includes other components such as common metadata and metrics management systems, specialized network systems, standards management, and centralized support for use of commercial cloud capabilities. Given the long-term requirements, and the rapid pace of information technology and changing expectations of the user community, EOSDIS has evolved continually over the past three decades. However, many challenges remain. Challenges in three key areas are addressed in this paper: managing volume and variety, enabling data discovery and access, and incorporating user feedback and concerns.